STUDI PENGGUNAAN ASBUTON PADA CAMPURAN ASPAL PANAS ASPHALT CONCRETE-WEARING COURSE (AC-WC) - Assiddiqie, Teguh Muhammad; Nurmayadi, Ade Rizki; Nurmayadi, Dicky (Universitas Perjuangan Tasikmalaya, 2024)
Abstract— Based on the Regulation of the Minister of PUPR No.18/PRT/M/2018 concerning the use of buton asphalt for road construction and preservation, further research was carried out to understand the characteristics of the Asphalt Concrete - Wearing Course (AC-WC) mixture. This study used Asbuton LGA type 50/30 with percentages of 3%, 6%, and 9% of the total weight of the mixture. There are a total of 42 test pieces, consisting of 30 for PKAO and 12 for KAO. The results showed that the mixture of AC-WC with 3% Asbuton LGA produced KAO of 5.7%, VIM Value 3.77%, VMA Value 14.96%, VFB Value 74.79%, Marshall Stability Value 1,366 Kg, Flow Value 3.15 mm, Marshall Quetient Value (MQ) 434 Kg/mm, and Immersion Value 90.33%. With the addition of 6% Asbuton LGA, KAO becomes 6%, VIM Value 4.87%, VMA Value 15.21%, VFB Value 67.97%, Marshall Stability Value 1,567 Kg, Flow Value 3.60 mm, MQ Value 435 Kg/mm, and Immersion Value 91.23%. The addition of 9% of Asbuton LGA resulted in a KAO of 6.3%, a VIM value of 7.11%, a VMA value of 18.43%, a VFB value of 61.43%, a Marshall Stability Value of 2,250 Kg, a Flow Value of 4.90 mm, an MQ Value of 459 Kg/mm, and an Immersion Value of 54.85%. The percentage of LGA Asbutone of 6% in the AC-WC mixture showed an increase in the Marshall stability value and Marshall immersion. Keywords — Asphalt Concrete – Wearing Course (AC-WC), Asbuton Lawele Granullar Asphalt (LGA), Marshall Test, Marshall Immersion, Marshall Quotient (MQ) Abstrak— Berdasarkan Peraturan Menteri PUPR No.18/PRT/M/2018 mengenai penggunaan aspal buton untuk pembangunan dan preservasi jalan, dilakukan penelitian lanjutan untuk memahami karakteristik campuran Asphalt Concrete - Wearing Course (AC-WC). Penelitian ini menggunakan Asbuton LGA tipe 50/30 dengan persentase 3%, 6%, dan 9% dari total berat campuran. Total terdapat 42 benda uji, terdiri dari 30 untuk PKAO dan 12 untuk KAO. Hasil penelitian menunjukkan bahwa campuran AC-WC dengan 3% Asbuton LGA menghasilkan KAO sebesar 5,7%, Nilai VIM 3,77%, Nilai VMA 14,96%, Nilai VFB 74,79%, Nilai Stabilitas Marshall 1.366 Kg, Nilai Flow 3,15 mm, Nilai Marshall Quetient (MQ) 434 Kg/mm, dan Nilai Immersion 90,33%. Dengan penambahan 6% Asbuton LGA, KAO menjadi 6%, Nilai VIM 4,87%, Nilai VMA 15,21%, Nilai VFB 67,97%, Nilai Stabilitas Marshall 1.567 Kg, Nilai Flow 3,60 mm, Nilai MQ 435 Kg/mm, dan Nilai Immersion 91,23%. Penambahan 9% Asbuton LGA menghasilkan KAO sebesar 6,3%, Nilai VIM 7,11%, Nilai VMA 18,43%, Nilai VFB 61,43%, Nilai Stabilitas Marshall 2.250 Kg, Nilai Flow 4,90 mm, Nilai MQ 459 Kg/mm, dan Nilai Immersion 54,85%. Persentase Asbuton LGA sebesar 6% pada campuran AC-WC menunjukkan peningkatan nilai stabilitas Marshall dan perendaman Marshall. Kata kunci — Asphalt Concrete – Wearing Course (AC-WC). Asbuton Lawele Granullar Asphalt (LGA), Marshall Test, Marshall Perendaman, Marshall Quotient (MQ)